Learn more about

Refine search


Results (38 matches)

  Download to        
Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
169.a.169.1 169.a \(y^2 + (x^3 + x + 1)y = x^5 + x^4\) $E_6$ $0$
196.a.21952.1 196.a \(y^2 + (x^2 + x)y = x^6 + 3x^5 + 6x^4 + 7x^3 + 6x^2 + 3x + 1\) $E_1$ $0$
249.a.249.1 249.a \(y^2 + (x^3 + 1)y = x^2 + x\) $\mathrm{USp}(4)$ $0$
249.a.6723.1 249.a \(y^2 + (x^3 + 1)y = -x^5 + x^3 + x^2 + 3x + 2\) $\mathrm{USp}(4)$ $0$
256.a.512.1 256.a \(y^2 + y = 2x^5 - 3x^4 + x^3 + x^2 - x\) $E_4$ $0$
277.a.277.1 277.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^2 - x\) $\mathrm{USp}(4)$ $0$
277.a.277.2 277.a \(y^2 + y = x^5 - 9x^4 + 14x^3 - 19x^2 + 11x - 6\) $\mathrm{USp}(4)$ $0$
294.a.294.1 294.a \(y^2 + (x^3 + 1)y = x^4 + x^2\) $\mathrm{SU}(2)\times\mathrm{SU}(2)$ $0$
294.a.8232.1 294.a \(y^2 + (x^3 + 1)y = -2x^4 + 4x^2 - 9x - 14\) $\mathrm{SU}(2)\times\mathrm{SU}(2)$ $0$
295.a.295.1 295.a \(y^2 + (x^3 + 1)y = -x^2\) $\mathrm{USp}(4)$ $0$
295.a.295.2 295.a \(y^2 + (x^2 + x + 1)y = x^5 - 40x^3 + 22x^2 + 389x - 608\) $\mathrm{USp}(4)$ $0$
324.a.648.1 324.a \(y^2 + (x^3 + x + 1)y = x^5 + 2x^4 + 2x^3 + x^2\) $E_3$ $0$
336.a.172032.1 336.a \(y^2 + (x^3 + x)y = -x^6 + 15x^4 - 75x^2 - 56\) $\mathrm{SU}(2)\times\mathrm{SU}(2)$ $0$
349.a.349.1 349.a \(y^2 + (x^3 + x^2 + x + 1)y = -x^3 - x^2\) $\mathrm{USp}(4)$ $0$
353.a.353.1 353.a \(y^2 + (x^3 + x + 1)y = x^2\) $\mathrm{USp}(4)$ $0$
360.a.6480.1 360.a \(y^2 + (x^3 + x)y = -3x^4 + 7x^2 - 5\) $\mathrm{SU}(2)\times\mathrm{SU}(2)$ $0$
363.a.11979.1 363.a \(y^2 + (x^2 + 1)y = x^5 + 2x^3 + 4x^2 + 2x\) $\mathrm{SU}(2)\times\mathrm{SU}(2)$ $0$
363.a.43923.1 363.a \(y^2 + x^2y = 11x^5 - 13x^4 - 7x^3 + 10x^2 + x - 2\) $\mathrm{SU}(2)\times\mathrm{SU}(2)$ $0$
388.a.776.1 388.a \(y^2 + (x^3 + x + 1)y = -x^4 + 2x^2 + x\) $\mathrm{USp}(4)$ $0$
389.a.389.1 389.a \(y^2 + (x^3 + x)y = x^5 - 2x^4 - 8x^3 + 16x + 7\) $\mathrm{USp}(4)$ $0$
389.a.389.2 389.a \(y^2 + (x + 1)y = x^5 + 2x^4 + 2x^3 + x^2\) $\mathrm{USp}(4)$ $0$
394.a.394.1 394.a \(y^2 + (x^3 + x)y = 2x^5 + x^4 - 12x^3 + 17x - 9\) $\mathrm{USp}(4)$ $0$
394.a.3152.1 394.a \(y^2 + (x + 1)y = -x^5\) $\mathrm{USp}(4)$ $0$
400.a.409600.1 400.a \(y^2 = x^6 + 4x^4 + 4x^2 + 1\) $E_1$ $0$
427.a.2989.1 427.a \(y^2 + (x^3 + 1)y = x^5 - x^4 - 5x^3 + 4x^2 + 4x - 4\) $\mathrm{USp}(4)$ $0$
448.a.448.2 448.a \(y^2 + (x^3 + x)y = -2x^4 + 7\) $N(\mathrm{U}(1)\times\mathrm{SU}(2))$ $0$
448.a.448.1 448.a \(y^2 + (x^3 + x)y = x^4 - 7\) $N(\mathrm{U}(1)\times\mathrm{SU}(2))$ $0$
450.a.2700.1 450.a \(y^2 + (x^3 + 1)y = x^5 + 3x^4 + 3x^3 + 3x^2 + x\) $\mathrm{SU}(2)\times\mathrm{SU}(2)$ $0$
450.a.36450.1 450.a \(y^2 + (x^3 + 1)y = x^5 - 4x^4 - 9x^3 + 28x^2 - 6x - 16\) $\mathrm{SU}(2)\times\mathrm{SU}(2)$ $0$
461.a.461.1 461.a \(y^2 + x^3y = x^5 - 3x^3 + 3x - 2\) $\mathrm{USp}(4)$ $0$
461.a.461.2 461.a \(y^2 + y = x^5 - x^4 - 39x^3 + 10x^2 + 272x - 306\) $\mathrm{USp}(4)$ $0$
464.a.464.1 464.a \(y^2 + (x + 1)y = -x^6 - 2x^5 - 2x^4 - x^3\) $\mathrm{USp}(4)$ $0$
464.a.29696.1 464.a \(y^2 + (x + 1)y = 8x^5 + 3x^4 - 4x^3 - 2x^2\) $\mathrm{USp}(4)$ $0$
464.a.29696.2 464.a \(y^2 + xy = 4x^5 + 33x^4 + 72x^3 + 16x^2 + x\) $\mathrm{USp}(4)$ $0$
472.a.944.1 472.a \(y^2 + (x^2 + 1)y = x^5 - x^4 - 2x^3 + x\) $\mathrm{USp}(4)$ $0$
472.a.60416.1 472.a \(y^2 + (x + 1)y = 8x^5 + 5x^4 + 4x^3 + 2x^2\) $\mathrm{USp}(4)$ $0$
476.a.952.1 476.a \(y^2 + (x^3 + 1)y = -5x^4 + 7x^3 + 25x^2 - 75x + 54\) $\mathrm{SU}(2)\times\mathrm{SU}(2)$ $0$
484.a.1936.1 484.a \(y^2 + y = x^6 + 2x^4 + x^2\) $\mathrm{SU}(2)\times\mathrm{SU}(2)$ $0$
  Download to